Sur le façonnement international des causes liées à la sexualité - Broqua C.; Fillieule O.; Roca I Escoda M. (Critique Internationale, 2016)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; droit; europe; histoire et politique; identités LGBTQIA2+; occident; premier cycle; périodes historiques; queer; régions géographiques; science politique et droit; sexualité; shm4000; systèmes d'oppressions; thématiques

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Les menaces au droit à l’avortement et à l’autonomie des femmes enceintes - Lemonde, Lucie (Les Cahiers de droit, 2009)
Après un bref survol de l’histoire récente de la criminalisation de l’avortement au Canada, l’auteure présente les divers projets de loi privés touchant d’une façon ou d’une autre le droit à l’avortement, principalement le projet no C-484 sur l’homicide foetal, pour en saisir les conséquences sur le droit canadien et sur l’autonomie des femmes pendant leur grossesse. Ces projets de loi se situent à l’intérieur d’une stratégie des opposants à l’avortement qui a essentiellement pour objet de faire reconnaître en droit canadien un droit à la vie et à la sécurité aux foetus et de remettre en question le libre choix des femmes en la matière. Suit une discussion sur l’instrumentalisation du droit pénal à des fins de contrôle social de questions d’ordre éthique. Le texte se termine par une réflexion concernant l’intérêt de l’État dans la protection des foetus. L’auteure soutient que toute intervention étatique doit se faire dans le respect des droits constitutionnels des femmes, soit leur droit à la vie, à la santé et à la liberté.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; avortement; canada; cours; discipline; droit; droits des femmes*; justice reproductive; justice sociale; patriarcat; pol4102; premier cycle; périodes historiques; régions géographiques; science politique et droit; sexisme; systèmes d'oppressions; thématiques

A broader vision of the reproductive rights movement: Fusing mainstream and latina feminism - Hooton, Angela (American University Journal of Gender, Social Policy & the Law, 2005)
https://digitalcommons.wcl.american.edu/cgi/viewcontent.cgi?article=1284&context=jgspl
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; discipline; discours dominant; droit; droits des femmes*; femmes* latino-américaines; histoire et politique; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; santé reproductive; science politique et droit; systèmes d'oppressions; thématiques; états-unis

Un genre trouble: le féminisme, la pornographie, la réforme du droit et la thèse de la reproduction de l'ordre social - Lacombe, D. (Déviance et société, 1992)
L'étude de la campagne de criminalisation de la pornographie au Canada, dans les années 1980, pose un défi au savoir conventionnel qui s'est développé, en sociologie et en criminologie, sur la réforme du droit. Ce savoir est l'argumentation selon laquelle les réformes, en dispersant le contrôle social, ne font que légitimer le système sans le modifier fondamentalement. Afin d'éviter l'essentialisme de ce savoir, j'ai utilisé une approche reflexive qui pense la relation entre la réforme du droit et le pouvoir comme à la fois contraignante et facilitante. L'établissement d'un lien entre la pornographie et la déviance sociale n'apparaît pas comme une construction sociale unifiée, mais comme un terrain contesté dans lequel se produisent des rapports de pouvoir complexes, et une multiplicité de stratégies de résistance. C'est dans ce sens que la réforme apparaît comme un mécanisme générateur des pratiques.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; canada; cours; criminologie; discipline; droit; féminisme pop; justice sociale; pornographie; premier cycle; périodes historiques; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; thématiques

Pornography and civil rights: a new day for women's equality - Dworkin, Andrea; MacKinnon, Catharine A. (Organizing Against Pornography, 1988)
"Pornography is central in creating and maintaining the civil inequality of the sexes. Pornography is a systematic practice of exploitation and subordination based on sex which differentially harms women. . . ." With those bold words began the groundbreaking local antipornography law drafted by writer Andrea Dworkin and lawyer Catharine A. MacKinnon. Their completely new legal approach–in which pornography is defined as sex discrimination and therefore a violation of civil rights–would allow anyone injured by pornography to fight back by filing a civil lawsuit against pornographers. First passed in December 1983 in Minneapolis, where it was supported by a grassroots coalition of women, people of color, neighborhood groups, and the city's welfare poor and working poor, this law has transformed the way people of conscience understand the devastating impact of pornography on women's right to equality. This new law also offers hope: an effective legal tool for making sex equality real. In this comprehensive and easy-to-read guidebook, now available on line, the coauthors of the anti-pornography civil-rights ordinance explain: How pornography hurts women and how and why the civil-rights ordinance would make a difference. Why the pornography is so important to women's equality. The truth about the antipornography civil-rights ordinance–what it is, what it does, what it means, how it works. Answers to the lies about it–lies that the media have spread to protect the pornography industry. What you can do to stop the pornographers and further women's equality. "The Ordinance does not take 'rights' away from anyone, . . . it takes the power to hurt women away from pornographers." –from Pornography and Civil Rights
Section: 142 pages ; 22 cm
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; droit; droits des femmes*; féminisme anti-porn; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique et droit; sex1911; sexualité; sofia; thématiques; violences; états-unis

Pornography, civil rights, and speech. (the 1984 Francis Biddle Memorial Lecture, Harvard Law School, April 5, 1984) (transcript) - MacKinnon, Catharine A. (Harvard Civil Rights-Civil Liberties Law Review)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; corps; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique et droit; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis